Analytical Approach to Find Effective Factors On Users' Attachment to Public Spaces (Case Study: Khayyam Street, Qazvin) - Chakhchian, Maryam (Journal of Urban Culture Research, 2025)
Different physical, social, activity and meaning aspects define public spaces as a social space. Several studies argue the relations between those main aspects and users’ attachment to such spaces. In this regard, this study tries to evaluate the significance of the relations between those four mentioned aspects in a selected public space based on the citizens' choice as a successful and desirable urban space. Data have been analyzed by SPSS software and the results indicate all of mentioned dimensions have a positive significance correlation users’ attachment to the place. Although, the result of path analysis shows activity aspect has an indirect effect on users’ attachment to the place the regression analysis result shows activity aspect has no significant effect on place attachment (P value> 0.05). In contrast, social aspect of the place which affected by other aspects, mainly by activity aspect; has the highest score (T=11.680). In addition, users’ attachment degree depends on the physical potential of space during time and involving to the place activities. In this regard, three indicators: aesthetic values, variety of activity and time play key role in formation of the users’ attachment in the public spaces.